Capital flight to Germany: Two alternative measures - Yin-Wong Cheung; Sven Steinkamp; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2019)
We use two measures to study two capital flight channels for Germany. One measure is based on the concept of trade misinvoicing and one on net claims and liabilities in the Eurosystem of central banks. For both measures, we propose refinements to enhance the assessment of capital flight. We find that capital flight towards Germany via these two channels has been quite sizable in the recent decade and can tally to about 2% of GDP annually. Regarding their determinants, we show that the two capital flight measures are driven by both common and measure-specific factors. Traditional determinants such as covered interest differentials only play a limited role, while crisis-specific factors such as economic policy uncertainty, the ECB collateral policy, as well as currency misalignment are driving factors of the investors' apparent flight-to-safety behavior.
Keywords: F3; F32; G15; 330; Illicit Capital Flight; Trade Misinvoicing; TARGET2 Balance; Flight-to-safety; Economic Policy Uncertainty